Dietary diversity and its associated factors among adolescent students of higher secondary schools in Tokha municipality. - Bhandari,Rama (2020)
ABSTRACT: Adolescents as those individuals between 10 and 19 years of age. In Nepal, adolescent represent 33.1% of the total population. Adolescence is considered as a nutritionally critical period of life. Healthy growth and development essentially need a balanced diet of nutrients and vitamins which includes a variety of foods from different food groups. Adequate dietary diversity is one of the major factors to ensure adequate nutrient intake in adolescents. Thus, the aim of the study is to assess the dietary diversity and its associated factors among adolescents of higher secondary schools in Tokha municipality. Descriptive cross-sectional study was conducted in selected higher secondary schools of Tokha municipality using two stage cluster sampling proportionate to size among 627 adolescents studying in class 11 and 12. The data was collected through selfadministered structured questionnaire regarding demographic, family related, nutritional knowledge, household food insecurity and 24-hour dietary recall tool to assess dietary diversity among adolescents. Anthropometric measurements were used to measure weight and height of adolescents. Data was entered in EpiData 3.1 and SPSS version 21 was used for analysis. The mean age of the adolescents was 17.2 with standard deviation 0.9. The female adolescents were more as compared to male (54.5%). Majority of adolescents belong to Brahmin/Chhetri ethnicity (47.0%). More than half (60.4%) of the participants belonged to a nuclear family. Less than half (47.8 %) of the adolescents had adequate nutritional knowledge. The majority (91.9%) of the participants were food secured while none were severely food insecure. Almost 31.7 % of the participants did not consume a diverse diet. Starchy staple diet was universal with the mean dietary diversity score of 6.42 ± 1.94. About 15.3% adolescents were overweight and 7.7% were underweight. Multivariate analysis revealed adolescents with father's higher education level (AOR: 2.00, 95% CI 1.08-3.68); adequate nutritional knowledge (AOR: 1.54, 95% CI 1.09-2.17); and adolescents who did not consume process food in last 24 hours (AOR: 1.79, 95% CI 1.16-2.75) were significantly associated with dietary diversity. Dietary diversity of the adolescents in Tokha municipality was more than 50%. Education level of father, nutritional knowledge of school adolescents and process food consumed in last 24 hours by school adolescents were significantly associated with dietary diversity of school adolescents. The period of adolescence just before marriage and childbearing is an opportunity that the health care system can utilize to provide nutrition education to increase dietary diversity and reduce the consumption of processed food among adolescents. Keywords: dietary diversity, adolescents, high school, body mass index